MANAJEMEN PEMBIAYAAN DALAM MENINGKATKAN SARANA DAN PRASARANA - Anisa Nur Afifah; Saiful Falah (Institut Ummul Quro Al-Islami Bogor, 2024)
Management of education financing is an important role in school quality, especially with regard to educational facilities and infrastructure. Where the success of learning is supported by the utilization of effective and efficient facilities and infrastructure. And to be able to manage and improve educational facilities and infrastructure, schools need to conduct education financing management. The aim of this research is to determine and analyze education financing management in improving facilities and infrastructure at SDN Cemplang 01 Bogor. This research method uses qualitative research by collecting data from observations, interviews and documentation. The results of this research show: 1) The education financing management implemented at SDN Cemplang 01 is in accordance with management functions. 2) The condition of the facilities and infrastructure at the school is quite good although there are some that need improvement. 3)Management of education financing in improving facilities and infrastructure in schools is through School Based Management (MBS). Based on the results of research carried out at SDN Cemplang 01 Bogor, it can be concluded that this school can improve facilities and infrastructure based on government standards through well-organized financing management and the application of the school-based management model (MBS) concept in financing its education.